Long‐Term Effects of Orthoses Use on the Changes of Foot and Ankle Joint Motions of Children With Spastic Cerebral Palsy. Issue 3 (1st September 2017) - Liu, Xue‐Cheng; Embrey, David; Tassone, Channing; Zvara, Kim; Brandsma, Brenna; Lyon, Roger; Goodfriend, Karin; Tarima, Sergey; Thometz, John
Abstract: Background: Orthoses commonly are prescribed to children with cerebral palsy (CP) to provide foot correction and to improve ambulatory function. Immediate effects of ankle foot orthosis (AFOs) have been investigated, but long‐term kinematic effects are lacking clinical evidence. Objective: To determine changes in 3‐dimensional ankle and foot segment motion in pediatric patients with CP between initial and follow‐up visits (18‐month average time differences) in both barefoot gait and gait with their AFO. We also investigated intravisit changes between barefoot and AFO gait. Design: A prospective cohort study. Setting: Children's Hospital of Wisconsin, Department of Orthopaedic Surgery, Medical College of Wisconsin. Patients: A total of 23 children with CP, mean age 10.5 years (6.2‐18.1 years) were clinically prescribed either a solid ankle foot orthotic (SAFO), hinged ankle foot orthotic (HAFO), or supramalleolar orthotic. Methods: Holes were cut in the study orthoses so that electromagnetic markers could be directly placed on the skin. A 6‐foot segment model was used. Outcome Measurements: Kinematic and kinetic data were recorded for each patient's initial and follow‐up visit (18‐month follow‐up average, 15‐20 months range). Results: For the SAFO group (gait with AFO), a significant decrease in dorsiflexion was found between the initial and third visit ( P = .008). Furthermore, the SAFO group (barefoot gait) had an increased eversion at the midfoot for most of the gait cycle ( P < .008). Sagittal forefoot range of motion was reduced for all 3 groups between the barefoot and AFO groups. Conclusion: The use of AFOs long term either maintained or improved foot deformities or dysfunction. Level of Evidence: Level II.